The value of constant a is -5
Further explanation:
We will use the comparison of co-efficient method for finding the value of a
So,
Given
![(x^2 - 3x + 4)(2x^2 +ax + 7)\\= x^2((2x^2 +ax + 7)-3x((2x^2 +ax + 7)+4(2x^2 +ax + 7)\\= 2x^4+ax^3+7x^2-6x^3-3ax^2-21x+8x^2+4ax+28\\Combining\ alike\ terms\\=2x^4+ax^3-6x^3+7x^2-3ax^2+8x^2-21x+4ax+28\\= 2x^4 +(a-6)x^3+(15-3a)x^2-(21-4a)x+28\\](https://tex.z-dn.net/?f=%28x%5E2%20-%203x%20%2B%204%29%282x%5E2%20%2Bax%20%2B%207%29%5C%5C%3D%20x%5E2%28%282x%5E2%20%2Bax%20%2B%207%29-3x%28%282x%5E2%20%2Bax%20%2B%207%29%2B4%282x%5E2%20%2Bax%20%2B%207%29%5C%5C%3D%202x%5E4%2Bax%5E3%2B7x%5E2-6x%5E3-3ax%5E2-21x%2B8x%5E2%2B4ax%2B28%5C%5CCombining%5C%20alike%5C%20terms%5C%5C%3D2x%5E4%2Bax%5E3-6x%5E3%2B7x%5E2-3ax%5E2%2B8x%5E2-21x%2B4ax%2B28%5C%5C%3D%202x%5E4%20%2B%28a-6%29x%5E3%2B%2815-3a%29x%5E2-%2821-4a%29x%2B28%5C%5C)
As it is given that
(x^2 - 3x + 4)(2x^2 +ax + 7) = 2x^4 -11x^3 +30x^2 -41x +28
In this case, co-efficient of variables will be equal, so we can compare the coefficients of x^3, x^2 or x
Comparing coefficient of x^3
![a-6 = -11\\a = -11+6\\a = -5](https://tex.z-dn.net/?f=a-6%20%3D%20-11%5C%5Ca%20%3D%20-11%2B6%5C%5Ca%20%3D%20-5)
So the value of constant a is -5
Keywords: Polynomials, factorization
Learn more about factorization at:
#LearnwithBrainly